(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2026)
This article presents a quadratic high-gain (QHG) transformerless DC-DC converter that integrates an active switched inductor (ASL) and a voltage doubler (VD) to achieve high voltage gain across a wide duty cycle range using a single switch. The design ensures steady input current, uses a simple continuous conduction mode (CCM), and lowers voltage stress on components—enabling the use of efficient low-resistance, low-voltage MOSFETs. By eliminating transformers and coupled inductors, it reduces size, weight, and leakage issues. Steady-state mathematical and efficiency analyses support the operating principles. A comparative study highlights its advantages, and a 100 W prototype is validated using a Simulink model.